Brain Reconstruction Across the Fish-Tetrapod Transition; Insights From Modern Amphibians - Clement, Alice M.; Mensforth, Corinne L.; Challands, T. J.; Collin, Shaun P.; Long, John A. (Frontiers in Ecology and Evolution, 2021)
The fish-tetrapod transition (which incorporates the related fin-limb and water-land transitions) are celebrated as one of the most important junctions in vertebrate evolution. Sarcopterygian fishes (the “lobe-fins”) are today represented by lungfishes and coelacanths, but during the Paleozoic they were much more diverse. It was some of these sarcopterygians, a lineage of the tetrapodomorph fishes, that gave rise to tetrapods (terrestrial vertebrates with limbs bearing digits). This spectacular leap took place during the Devonian Period. Due to the nature of preservation, it is the hard parts of an animal’s body that are most likely to fossilize, while soft tissues such as muscular and brain tissues, typically fail to do so. Thus, our understanding of the adaptations of the hard skeletal structures of vertebrates is considerably greater than that of the soft tissue systems. Fortunately, the braincases of early vertebrates are often ossified and thereby have the potential to provide detailed morphological information. However, the correspondence between brain and braincase has historically been considered poor in most “lower” vertebrates and consequently neglected in such studies of brain evolution. Despite this, recent work documenting the spatial relationship in extant basal sarcopterygians (coelacanth, lungfish, axolotl and salamander) has highlighted that this is not uniformly the case. Herein, we quantify and illustrate the brain-braincase relationship in four additional extant basal tetrapod exemplars: neobatrachian anurans (frogs) Breviceps poweri and Ceratophrys ornata; and gymnophionans (caecilians) Gegeneophis ramaswamii and Rhinatrema bivittatum. We show that anurans and caecilians appear to have brains that fill their braincases to a similar degree to that of lungfishes and salamanders, but not coelacanth. Ceratophrys has considerably lower correspondence between the brain and endocast in the olfactory tract and mesencephalic regions, while Breviceps has low correspondence along its ventral endocranial margin. The brains of caecilians reflect their cranial cavities most closely (vol. ~70%). The telencephalon is tightly fitted within the endocast in all four taxa. Our findings highlight the need to adequately assess the brain-braincase relationship in a broad range of vertebrates, in order to inform neural reconstructions of fossil taxa using the Extant Phylogenetic Bracket approach and future studies of brain evolution.